2013
DOI: 10.1590/s0100-83582013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Globe fringerush (Fimbristylis miliacea) cross resistance to als-inhibitor herbicides under field conditions in irrigated rice in the south of Brazil

Abstract: ALS-inhibiting herbicides usually provide adequate weed control in irrigated rice fields. After consecutive years of use, the Cyperaceae species, globe fringerush (Fimbristylis miliacea) began to show resistance to ALS (acetolactate synthase) inhibitors. Globe fringerush is one of the most problematic herbicide-resistant weeds in irrigated rice in the state of Santa Catarina in the South of Brazil. The objective of this research was to examine cross resistance of globe fringerush to ALS inhibitors, under field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…and sedges (Cyperus spp.) (Galon et al, 2008;Roso et al, 2010;Matzenbacher et al, 2013;Schaedler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…and sedges (Cyperus spp.) (Galon et al, 2008;Roso et al, 2010;Matzenbacher et al, 2013;Schaedler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies developed in southern Brazil identified F. miliacea as a species with cross-resistance to the ALS-inhibiting herbicides bispyribac-sodium, ethoxysulfuron, pyrazosulfuron-ethyl, penoxsulam, imazethapyr, imazapic, and imazapyr (Sosbai, 2012;Schaedler et al, 2013). In this sense, unlike this information, the results obtained in the present study with the in-tank mixture of bispyribac-sodium + metsulfuronmethyl, both ALS-inhibiting herbicides, did not characterize resistance behavior for this species in the studied population, and no information on the association of these herbicides was found in the literature, for comparison purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Ortiz et al (2012), in a dose-response study, identified ten pyrazosulfuron-ethyl resistant populations of F. miliaceae collected in irrigated rice fields in the state of Guárico, Venezuela. In Brazil, Schaedler et al (2013) also reported the occurrence of F. miliaceae, in the state of Santa Catarina, infesting irrigated rice crop, presenting cross-resistance to the herbicides pyrazosulfuron-ethyl, penoxsulam, bispyribac-sodium, and ethoxysulfuron, being all of them acetolactate synthase (ALS) enzyme inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of cross-resistance to ALS inhibitors have been reported in cyperaceae occurring in irrigated rice, such as Cyperus difformis (Galon et al, 2008), Fimbristylis miliacea (Schaedler et al, 2013), Schoenoplectus juncoides (Sada et al 2013) and, more recently, Cyperus iria (Riar et al, 2015). It is important to determine the cross-resistance spectrum, since this information may collaborate with technicians/farmers in order to select alternative herbicides for an effective weed management (Deng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%